Roads Improvement for Poverty Alleviation in China - Hajj, Hatim (World Bank, Washington, DC, 2014)
In China, rural road improvements have been integrated with major highway projects, implemented with World Bank assistance, during 1995-98. These improvements were called, "Roads Improvement for Poverty Alleviation (RIPA)," and were linked to on-going poverty alleviation programs. These Bank assisted projects are in five provinces of China: Gansu, Henan, Inner Mongolia, Ningxia, and Shaanxi. RIPA concentrates on linking those rural villages and townships which do not currently have basic all weather access to the existing road networks of a higher order. This report focuses, from a conceptual analytical, and methodological viewpoint upon the RIPA experience in the above-mentioned Bank-assisted projects in China. It also describes the background to poverty alleviation programs and the linkages to roads improvement in China. It reviews current practices and recommends appropriate design standards, and a framework of monitoring indicators. This report focuses on those road systems which provide easy access to the rural population in designated poor counties in China. The primary objectives are to provide a conceptual framework for RIPA, describe Chinese poverty alleviation policies linked to roads improvement, and discuss the potential for replicating RIPA in other countries. Other aims are to develop screening and an analytical framework for appraising road systems, and appropriately design and monitor different classes of RIPA roads.